The Influencee of Human Resource Development on Employee Performance at PT Pelindo Terminal Petikemas New Makassar - Jayadi; Widia, Widia; Dian Gita Utami (Jurusan Administrasi Niaga, Politeknik Negeri Ujung Pandang, 2025)
In the era of increasingly dynamic business competition, human resource development has become a crucial factor in improving employee performance and ensuring organizational sustainability. The significance of this study lies in its contribution to providing an overview of the effectiveness of human resource development and identifying its influence on employee performance at PT Pelindo Terminal Petikemas New Makassar. This study aims to determine the effect of human resource development on employee performance at PT Pelindo Terminal Petikemas New Makassar. The research population consisted of 149 employees, with a sample of 60 respondents determined using the Slovin formula and the proportionate stratified random sampling technique. Data were collected through questionnaires and interviews, then analyzed using validity and reliability tests, simple linear regression, the coefficient of determination, and the t-test with the assistance of SPSS version 25. The results of this study indicated that human resource development, measured through education and training indicators, has a positive and significant effect on employee performance, which is measured through job knowledge, teamwork ability, and independent creativity. The coefficient of determination also shows that human resources contribute significantly to the improvement of employee performance.